Full-field interferometry using infinity corrected optics - Charrett, Thomas O. H.; Tatam, Ralph P. (IOP Publishing, 2015)
In this paper the construction of full-field (imaging) interferometers using infinity corrected optics commonly used in microscopy is discussed, with an emphasis on self-mixing interferometry configurations where the imaged light field is mixed with itself rather than a reference wave. Such configurations are used in speckle shearing interferometry, flow visualisation and quantitative flow measurement. The critical considerations for constructing path-length imbalanced full-field interferometers for these and similar applications are discussed, expressions are derived for key calculations and interferograms from example interferometers are presented. These include the concept of balancing the infinity-spaces of the two arms via the use of a glass block to minimise the optical path difference variation across the interferogram and ensure adequate sampling of the fringes on the detector. Further, the use of tilted glass blocks in single-pass and double-pass arrangements is detailed for the generation and control of spatial carrier fringes without extensive realignment of the interferometer, and for phase shifting.
Keywords: Infinity corrected optical systems; Interferometric imaging; Fringe analysis; Shearography; Planar Doppler velocimetry; PDV; Doppler global velocimetry; DGV